Geology of the Himalayan belt : deformation, metamorphism, stratigraphy - Chakrabarti, B. K. (Amsterdam, Netherlands : Elsevier, 2016)
Geology of the Himalayan Belt: Deformation, Metamorphism, Stratigraphy presents sophisticated metamorphic and igneous rock data across various Himalayan geographic sectors, capturing their petrography, metamorphism, structure, mineralization, and regional tectonic research. With an east-west extension of about 3000 kilometers and numerous 8000 meter peaks, the Himalayas are the most spectacular mountain ranges on earth. Since the 19th century, they have provided a testing ground of global importance for the development of geodynamic concepts, from isostasy over continental collision, to more recently, feedback mechanisms between tectonics and climate. This book collects the broad range of data that's been gathered on the Himalayas over the past 50 years, providing a comprehensive analysis and interpretation on the available data that brings the scientific community a better understanding of the geological diversity and structure of the Himalayan belt, along with new techniques that have applications in a host of global geological settings.
6.2.2 Marsyandi-Darondi-Burhi Gandaki River Domain -- 6.2.3 Trisuli-Langtang River Sections -- 6.2.4 Kathmandu-Sheopuri-Gosaikund Sector -- 6.2.5 Everest-Makalu Domain and the Okhaldunga, Arun, and Tamur Windows (Eastern Nepal) -- 6.2.5.1 Arun Window -- 6.2.5.2 Everest-Makalu-Arun River Domain -- 7 -- Darjeeling-Sikkim Himalaya -- 7.1 REGIONAL GEOLOGY -- 7.2 STRUCTURE AND METAMORPHISM OF THE CRYSTALLINES -- 7.2.1 Recent Studies -- 7.2.1.1 The Lesser Himalayan Sequence -- 7.2.1.2 Structure of the Rangit Window -- 7.2.1.3 Movement of Thrust Sheet -- 8 -- Bhutan Himalaya -- 8.1 REGIONAL GEOLOGY.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 21, 2016).
Keywords: Geology -- Himalaya Mountains Region; SCIENCE -- Earth Sciences -- General; Geology; Himalaya Mountains Region; Geologie; Himalaja; Electronic books; Electronic book